KETERKAITAN KURS DAN TINGKAT BUNGA - Tarsilohadi, Edy Rahmanryo (Universitas Muhammdaiyah Surakarta, 2005)
The deep depreciation of the Rupiah from August 1997 through 1998 poses a big problem for domestic economic. Because the Indonesia economic faced with the international trade deficit and the balance of capital surplus, has given rise to the depreciation of Rupiah. At the same time, the banking sector has been higher interest rates. Examination of the data indicates causal linkage between the exchange rate of rupiah and the interest rate, vice versa. This result reflects the weakness of the real and monetary sectors in Indonesia. To avoid the failure economic, will need the contribution monetary and others policies make to that environment are critical.